The effect of pore characteristics on the bonding properties of steam-cured concrete and GFRP bars - Zhang, Kai; Yang, Wenrui; Tang, Zhiyi; Wu, Weiwei; Quan, Weijie; Wang, Shiyu (Frontiers in Materials, 2023)
Steam cured concrete prefabricated components has the advantages of short construction period, less environmental pollution, convenient construction and low cost, and is widely used in high-speed railway projects. However, the changes of later strength, capillary water absorption and pore distribution led to the reduction of durability of steam-curing concrete and accelerated the damage speed of GFRP bars and bond performance between concrete and GFRP bars. In this study, the method of steam curing is adopted to simulate the damage of components caused by actual steam curing environment. The influence of pore characteristics on the bonding properties of steam cured concrete and GFRP steel bar is analyzed from both micro and macro perspectives. Analysis method combining pore characteristics with bonding strength.The test results showed that the hydration products of concrete were unaffected, but the density of the hydration products changed due to the steam curing. The porosity of the steam-cured concrete was much higher than that of the standard-cured concrete. The number of gel pores smaller than 20 nm accounted for 12.27% of the total number of pores on average, which was about twice the proportion of the gel pores of this size in the standard-cured concrete. The proportion of harmful voids with pore size of 50-200 nm and greater than 200 nm is higher than that of standard curing concrete. The bond strength of the steam-cured concrete and GFRP bars was 30% lower than that of the standard-cured concrete. With the change of the thickness of the concrete cover and the diameter of GFRP bars, the bond strength changed significantly.Based on the analysis of the test data, a predictive model of the bond strength deterioration for the steam-cured concrete and GFRP bars was established. The model fully accounted for influence factors such as the porosity, diameter, anchor length, and concrete strength.